The Effect of Compensation, Training, and Work Environment on Employee Performance Perumda BPR Bank Daerah Lamongan (BDL) - Abdi, Abdillah Hanif Isna S; Farida, Siti Ning (International Journal of Economics Development Research (IJEDR), 2024)
Human resources (HR) have an important role in determining company performance, especially in the competitive banking sector. Compensation, training, and work environment are factors that can affect employee performance. This study intends to analyse the effect of Compensation, Training, and Work Environment on Employee Performance of Perumda BPR Bank Daerah Lamongan (BDL). The data used in this study are secondary and primary data. The population in the study were all permanent employees of the Lamongan Regional Bank (BDL). The sampling technique used was Proportional Stratified Random Sampling and obtained 65 samples from 184 employees using the Slovin formula. This study uses multiple linear regression analysis. The results of this study indicate that compensation, training, and work environment have a positive and significant effect on the performance of Perumda BPR Bank Daerah Lamongan (BDL) employees. These findings contribute to management to be able to improve employee performance within the company.